Ultrasonic dissection versus conventional electrocautery during gastrectomy for gastric cancer: A meta-analysis of randomized controlled trials. Issue 4 (April 2015) - Sun, Z.C.; Xu, W.G.; Xiao, X.M.; Yu, W.H.; Xu, D.M.; Xu, H.M.; Gao, H.L.; Wang, R.X.
Abstract Objective Use of ultrasonic surgical instrument is gaining popularity for dissection and coagulation in open surgery. However, there is still no consensus on the efficacy and safety of its use compared with conventional surgical technique in open gastrectomy for gastric cancer. The aim of this meta-analysis was to evaluate the role and surgical outcomes of ultrasonic dissection (UD) compared with conventional electrocautery (EC). Methods A systematic literature search was performed to identify all studies comparing UD and EC in gastric cancer surgery. Intraoperative and postoperative outcomes were compared using weighted mean differences (WMDs) and odds ratios (ORs). Results Five studies were included in this meta-analysis, comprising 489 patients. Meta-analysis results showed that compared with EC, UD was associated with significantly shorter operation time (P = 0.03), less intraoperative blood loss (P = 0.002), lower morbidity (P = 0.02), and reduced postoperative hospital stay (P = 0.03). However, there was no significant difference between the two surgical techniques with regards to postoperative abdominal drainage (P = 0.17), and total cost in hospital (P = 0.59). Conclusions Compared to EC, the use of UD during open gastrectomy can provide several improved outcomes for operation time, intraoperative blood loss, overall morbidity, and postoperative hospital stay. It appears that UD can be used instead of conventional EC in open gastric cancer surgery, although more larger trials with long follow-up should be performed.